2013
DOI: 10.1007/s00270-013-0659-2
|View full text |Cite
|
Sign up to set email alerts
|

Embolization of the Internal Iliac Artery Before EVAR: Is It Effective? Is It Safe? Which Technique Should Be Used?

Abstract: IIA embolization is technically successful and effective in preventing significant type 2 endoleak in the majority of cases. It is a relatively safe procedure without major complications, but the incidence of buttock claudication and erectile dysfunction remain relatively high, and patients should be consented appropriately. There is no significant benefit for adopting a particular embolization technique, but there is a tendency towards reduced pelvic ischaemia with proximal embolization. Four cases of type II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
6
21
1
1
Order By: Relevance
“…15 In accordance with their results, we did not find a significant difference between ProxEmbX of unaffected IIA and DistEmbX of aneurysmatic IIA; however, in our study, another scenario in each group was reflected. Chun et al 15 reported pelvic ischaemia in 30% of patients with ProxEmbX and in 52% of patients with DistEmbX without statistic difference. In a recent systemic review of literature, Rayt et al 19 showed an overall incidence of buttock claudication and erectile dysfunction of 28% and 17%, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…15 In accordance with their results, we did not find a significant difference between ProxEmbX of unaffected IIA and DistEmbX of aneurysmatic IIA; however, in our study, another scenario in each group was reflected. Chun et al 15 reported pelvic ischaemia in 30% of patients with ProxEmbX and in 52% of patients with DistEmbX without statistic difference. In a recent systemic review of literature, Rayt et al 19 showed an overall incidence of buttock claudication and erectile dysfunction of 28% and 17%, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies reported high technical success rates. 8,15,21,22,25 The number of coils used varies from patient to patient. Coil embolization may be complicated by compromising collateral vessels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no general consensus regarding the use of either sequential or staged embolization of both internal iliac arteries, but in a majority of centres where both internal iliac arteries should be embolized, the staged strategy is most common [9] . Proximal embolization of the internal iliac artery is strongly advised to allow for collateral circulation [10] .…”
Section: Occlusion Of the Internal Iliac Arterymentioning
confidence: 99%